1994
DOI: 10.1002/app.1994.070510217
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of silk fibers modified with dibasic acid anhydrides

Abstract: SYNOPSISThe objective of this study was to investigate the physical properties of silk fibers modified with dibasic acid anhydrides. These are potentially attractive modifying agents to reduce the rate of photoyellowing of silk during and following UV irradiation. Several analytical techniques were employed, which included the measurement of the basic mechanical properties (tensile strength and elongation at break), equilibrium regain, amino acid analysis, dynamic viscoelastic measurements, X-ray diffractometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Higher extents of acylation were attained by using other aliphatic acid anhydrides, such as succinic and glutaric anhydrides. 15 On the basis of the kinetic data shown in Figure 1, samples of silk fabrics modified with TA or acylated with EDTA-dianhydride with similar weight gains (5, 12, and 17%) were prepared for the metal uptake tests.…”
Section: Chemical Modification Of Silkmentioning
confidence: 99%
“…Higher extents of acylation were attained by using other aliphatic acid anhydrides, such as succinic and glutaric anhydrides. 15 On the basis of the kinetic data shown in Figure 1, samples of silk fabrics modified with TA or acylated with EDTA-dianhydride with similar weight gains (5, 12, and 17%) were prepared for the metal uptake tests.…”
Section: Chemical Modification Of Silkmentioning
confidence: 99%
“…Investigationshave been carried out by many workers for improving some of the inferior performance properties of silk such as photoyellowing, wrinkle recovery, abrasion resistance, and wash and wear by adopting various graft copolymerization and/or chemical‐modification techniques 1, 2. Epoxides,3 glutaraldehyde,4 glycol diglycidyl ether,5 and aliphatic and aromatic dibasic acid anhydrides6, 7 have been used for chemical modification of silk and wool 8. Graft copolymerization as such has become an attractive means of chemical modification of protein fibers, since such treatments, in general, improve some of the disadvantages associated with these fibers 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the acylation with dibasic acid anhydrides appeared particularly attractive, because a slight chemical modification resulted in a significant change of the dyeing properties of silk and other animal protein fibem6y7 We studied the physical properties and the thermal behavior of silk fibers, modified by acylation, and found that dibasic acid anhydrides were reactive mainly towards basic amino acid residues. 8 Several vinyl monomers, such as methyl methacrylate (MMA) ,' methacrylamide (MAA) ,lo 2-hydroxy-ethyl methacrylate ( HEMA), " ethoxy-ethyl metacrylate ( ETMA) , l2 methacrylonitrile (MAN), l3 and styrene (St) l4 have been used as grafting agents, and some of them were successfully applied on the industrial scale for silk processing, that is, silk grafted with MAA. The physical and mechanical properties, as well as the' structural characteristics, of silk fibers, grafted with different vinyl monomers, have been reported.…”
Section: Introductionmentioning
confidence: 99%